Local plasmons contribution into photocurrent of Au/GaAs surface barrier structure with Au nanoparticles on interface - Mamykin, S.; Dmitruk, N.; Korovin, A.; Naumenko, D.; Dmytruk, A.; Park, Yeon-Su (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Au/SiO₂ core-shell nanoparticles have been used to increase the photocurrent in the surface barrier structure Au/GaAs. The method for theoretical calculation of interaction between light and the system of ordered nanoparticles placed on the surface barrier structures has been proposed. Local plasmons excited in the nanoparticles produce additional carriers due to scattering, prolonged interaction with semiconductor and enhanced evanescent electromagnetic field, thus they increase the photocurrent.